Star trek IV : the voyage home [videorecording (Blu-Ray)] - Meerson, Steve; Nimoy, Leonard; Shatner, William; Kelley, DeForest, 1920-1999; Hicks, Catherine, 1951-; Doohan, James; Koenig, Walter, 1936-; Takei, George, 1937-; Nichols, Nichelle (Paramount Home Entertainment, 2009)
The command crew of the Enterprise travels back in time to bring two humpback whales to the future Earth to save the planet from being destroyed by a mysterious alien probe.